EFEKTIFITAS APLIKASI PUPUK SISTEM TABUR DAN SACHET TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensisi Jacq) - Mardiana Wahyuni (Jurnal Agro Estate, 2018)
The productivity of oil palm plants is influenced by genetic factor planting materials, soil, climate, cultivation and plant maintenance. Nursery is the first step to prepare the prime plant material. In the implementation of the nursery, fertilization is one important maintenance factor and should be done with reference to 4T (Exactly Types, Dosage, Time and Method). Loss of fertilizer is an important thing to be controlled. This research is a conservation action by packing fertilizer in sachet bag and conservation treatment. The research was conducted in August 2016- June 2017 at STIPAP. The study used 2x2 Factorial Design with the first Factor of Broadcast System, Sachet and the second factor was with and without conservation. The best treatment was SK1 Sachet application and conservation increased leaf number 14,44 (6%), girth 18,60 cm (14%) and chlorophyll 63,16 (20%).